Childhood family risks and mental health of older adults in China: The moderating effect of age - Xinzhu, Wang (Frontiers in Psychology, 2023)
Introduction Childhood family risks (CFRs) are believed to have long-arm effects on people's mental health. However, it is unclear whether age can alleviate these long-arm effects. Aim This study aimed to explore the relationship between CFRs and the mental health of older adults (mean [M] = 62.10, standard deviation [SD] = 8.02) in China and investigate whether age could moderate this relationship. Methods This cross-sectional, survey-based study used data from the Chinese General Social Survey conducted in 2015, and the data of 4,237 respondents were included in the final analysis. Mental health was measured by two items, namely negative and positive emotions. The step-by-step regression procedure and moderation analysis technique were used. Results For older adults in China, CFRs were significantly negatively associated with their mental health (β = −0.046, t = −2.690, p < 0.01), age was positively correlated with their mental health (β = 0.115, t = 7.157, p < 0.01), and age significantly moderated the relationship between CFRs and mental health (β = 0.277, t = 2.172, p < 0.05). As age increases, the correlation between CFRs and mental health decreases, and when age is one SD above the M, CFRs are no longer significantly associated with the mental health level (bsimple = −0.01, t = −0.077, p > 0.05). Conclusion This study showed that CFRs were negatively associated with the mental health level of older Chinese adults, and age could significantly moderate the association. Therefore, it is essential to take preventive measures in advance to protect people's mental health and teach older adults to use emotion-regulation techniques to weaken the association between CFRs and mental health.